2020
DOI: 10.5210/spir.v2018i0.10504
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Information Production Process on Experience and Evaluation

Abstract: Research to date on the value of information has mostly focused on the consumption side of information, namely, that consumers need to experience information in order to evaluate it. When it comes to digital media, users have multiple roles. In this context, materiality is applied to assess the role that technological components play in the interaction between user and digital media. The concurrent consumption and production of information raises questions as to the influence of information production on infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…For example, decisions regarding health care or strategic decisions. Further to the findings obtained in the experiments-A positive relationship was found between the number of peers producing information and the probability to make a major change in decision, in line with the diminishing value of information (Rusho & Raban, 2018. Self-production, which leads to the highest value perception, exemplifies the low probability to make a major change in decision following the production process.…”
Section: Future Worksupporting
confidence: 65%
See 1 more Smart Citation
“…For example, decisions regarding health care or strategic decisions. Further to the findings obtained in the experiments-A positive relationship was found between the number of peers producing information and the probability to make a major change in decision, in line with the diminishing value of information (Rusho & Raban, 2018. Self-production, which leads to the highest value perception, exemplifies the low probability to make a major change in decision following the production process.…”
Section: Future Worksupporting
confidence: 65%
“…In the present research, information production experience follows a circular five-stage process in which an information product, a presentation, is created (Rusho & Raban, 2019). In previous research, we showed that when individuals are engaged in producing information they develop a higher evaluation of their self-created information product as compared to an identical information product created for them (Rusho & Raban, 2018. This is a form of expression of the Ikea Effect as applied to digital information (Norton et al, 2012).…”
Section: Information Consumption and Production As Web Experiencesmentioning
confidence: 61%
“…A prior study examined whether the IKEA effect, which usually applies to physical products, occurs in the production of information goods by individuals. The results confirmed that the experience of individually producing information led to higher evaluation of the information than did consuming it (Rusho & Raban, 2020, 2018a, 2018b). Rusho and Raban define information production process as a circular five‐stage model: specification, design, implementation, validation, and evolution.…”
Section: Theory Developmentsupporting
confidence: 61%
“…Information experience enhances value perception (Rusho & Raban, 2018a, 2018b). This dynamic nature of information evaluation refers to the experiential aspect of information goods, which must be experienced in order to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation